UNDERSTANDING TRANSGENDER REPOSITIONING IN THE PERSPECTIVE OF HADITH - Mubarak, Husni (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2023)
Transgender is still a hotly discussed phenomenon among the public. It deviates against human nature because it violates human nature, namely the likeness of the opposite sex, and has received a lot of rejection from Muslims. This article offers an understanding of the factors behind the occurrence of transgender as well as the repositioning of transgender based on the Prophet’s hadith, which is expected to inhibit the rate of development of transgender. This research will examine the hadiths prohibiting the likeness of the opposite sex, which are then analyzed using the hermeneutic method to gain an understanding of the repositioning of transgender people based on the guidance of prophetic traditions. The findings of this study indicate that Transgender is an act that is considered deviant by individuals, both male and female, by imitating the appearance of the opposite sex. This behavior is considered a social disease, despicable behavior, and major sin that can disrupt society and is categorized as a violence of provisions of God, so it needs to be avoided; where transgender can occur because several factors influence it. The deviant behavior of a man resembles the opposite sex so that the Prophet ordered to punish the person by exiling, which can be interpreted as a repositioning process. Some of the Prophet’s traditions discuss the likeness of the opposite sex, which indicates that such acts occurred during the Prophet’s time and can be considered as a step to return deviant individuals to their original nature. The findings of this study can have implications for the repositioning process and efforts to prevent transgender.[Transgender masih menjadi fenomena yang hangat diperbincangkan di kalangan masyarakat, karena menyimpang menyalahi kodrat manusia yaitu penyerupaan terhadap lawan jenis dan mendapat banyak penolakan dari umat muslim. Artikel ini menawarkan sebuah pemahaman mengenai faktor-faktor yang melatarbelakangi terjadinya transgender serta reposisi transgender berdasarkan hadis Nabi, yang diharapkan dapat menghambat laju perkembangan transgender. Penelitian ini akan mengkaji hadis-hadis larangan penyerupaan terhadap lawan jenis yang kemudian dianalisis menggunakan metode hermeneutik untuk mendapatkan pemahaman mengenai reposisi transgender berdasarkan dengan petunjuk hadis Nabi. Temuan dari penelitian ini menunjukkan bahwa transgender merupakan suatu perbuatan yang dianggap menyimpang oleh individu, baik laki-laki maupun perempuan, dengan meniru penampilan lawan jenis. Perilaku tersebut dianggap sebagai penyakit sosial, perilaku tercela, dan dosa besar yang dapat meresahkan masyarakat dan dikategorikan sebagai pelanggaran ketentuan Tuhan, sehingga perlu dihindari; dimana transgender bisa terjadi karena beberapa faktor yang mempengaruhinya. Perilaku menyimpang dari seorang laki-laki ini menyerupai lawan jenis sehingga Nabi memerintahkan untuk menghukum orang tersebut dengan melakukan pengasingan yang dapat dimaknai dengan proses reposisi. Beberapa hadis Nabi membahas penyerupaan dengan lawan jenis, yang menandakan bahwa perbuatan tersebut terjadi pada masa Nabi dan dapat dianggap sebagai langkah mengembalikan individu yang menyimpang ke sifat aslinya. Temuan dari penelitian ini dapat berimplikasi pada proses reposisi dan upaya untuk mencegah terjadinya transgender.]